Political Awareness of Students towards the 2023 House of Representatives Election: A Case Study of Kalasin University Students - Awaram, Phatcharathida; Prommajeen, Rutchaneekon; Sinlapachai, Chamaiphon; Chaiyaphum, Akkarajet (Journal of Graduate MCU KhonKaen Campus, 2025)
This study aimed to 1. examine the level of political awareness among students at Kalasin University regarding the 2023 House of Representatives election, and 2. analyze factors affecting political awareness and propose strategies for promoting political engagement among the younger generation. A mixed-methods research approach was employed, with data collected from 341 students through questionnaires and in-depth interviews conducted with 15 participants. The findings revealed that students demonstrated a high level of political awareness (M = 3.92). Political news awareness showed the highest mean score (M = 4.00), followed by political culture (M = 3.98), political understanding and interest (M = 3.97), political participation (M = 3.86), and political socialization institutions (M = 3.84). Factors influencing political awareness were at a high level (M = 3.91), with information-seeking behavior having the strongest influence (M = 3.95). In-depth interviews identified key factors influencing voting decisions: policies addressing youth concerns, digital media information consumption, fear of losing future rights, and family influence. The study indicates that Generation Z exhibits different political awareness behaviors compared to previous generations, with online media and social media playing crucial roles in accessing political information. Key recommendations include: the government should develop youth-specific policies, utilize digital media for political communication, and enhance transparency; educational institutions should modernize political curricula, promote media literacy, and create platforms for political discourse.